Net Social Expenditure 2nd Edition - Adema, Willem (OECD Labour Market and Social Policy Occasional Papers, 2001)
This document is the 2nd edition of the Net Social Expenditure paper published in 1999 (Adema, 1999). It contains an overview of net (after tax) public and private social expenditure indicators. These indicators have been developed to supplement available historical information on gross social expenditure trends by accounting for the varying impact of the tax system across countries. Tax systems can affect social spending in three ways: Governments levy direct taxes and social security contributions on cash transfers. Governments levy indirect taxes on goods and services bought by benefit recipients. Governments may award tax advantages similar to cash benefits and/or grant tax concessions aiming to stimulate the provision of private social benefits. The document summarises the methodological framework as previously developed, but extends coverage to eighteen countries for which information for 1997 is now available: Australia, Austria, Belgium, Canada, the Czech ...